Northward shifts of Canadian late deglacial drainage routes caused a stronger and warmer Canaries Current that enabled Holocene monsoons and a savanna on the western Sahara - Robert G. Johnson, (JOURNAL OF ADVANCES IN NATURAL SCIENCES, 2020)
This paper proposes an explanation for the well-watered savanna on the presently barren western Sahara Desert during the mid-Holocene and near the ends of other earlier Canadian deglaciations. Between 7,500 and 4,000 years before present, a humidity index indicates moist conditions and a savanna in the western Sahara. During this interval, a stronger and warmer Canaries Current return flow of the Gulf Stream nullified the effect of cold water that upwells off the northwest African coast due to the westward movement of surface water by trade winds. The return flow was stronger than today because less eastward Gulf Stream flow was lost to the northward flow of the Atlantic Meridional Overturning Current. The Canaries Current was warmer than today because cold southern Canadian meltwater no longer entered the Gulf Stream, and the high latitude climate was warmer then. Similar conditions probably prevailed at the ends of many other deglaciations, which were separated by 20,000 to 70,000 years due to orbital factors and variable glaciation. The savanna connections across the Sahara would have allowed each Hominin population to evolve in the isolated Moroccan-Algerian coastal zone to extend its range into the larger Africa. The intermittent savannas could therefore have played a significant role in the evolution of the many Hominin species found in the African fossil record over the last three million years.